Aircraft Emissions in Airports - The LPPT Case - Barata, Jorge M M (2012)
A new methodology to predict the aircraft emissions in airport vicinity is presented. The application to the LPPT airport is discussed, and the results revealed that the emissions are dependent on the flight schedules and strongly affected by the aircraft/engine combinations.